Efeito da administração de eritropoetina e de vetores recombinantes em parâmetros reprodutivos de coelhos - Collares, Thais Farias (2010)
The administration of recombinant proteins is being used in sport as gene doping. In medicine, a recent therapeutic technique is the genetic therapy, which, up to this moment, shows results that indicate its efficiency in the treatment of some diseases. Recently, the potential for misuse of gene therapy among athletes has called the attention of scientists and sports regulating organs. The transfer of genes that could enhance athletic performance was named gene doping. The most important candidate genes for gene doping are Erythropoietin (EPO), vascular endothelial growth factor (VEGF), insulin-like growth factor I (IGF-1) and myostatin blockers. Nevertheless, gene therapy presents adverse indicators, such as inflammatory response and lack of control of gene activation. It is probable that in healthy individuals such problems would be aggravated. There are still no conclusive tests capable of detecting gene doping. However, recent researches have studied promising strategies. The reflection of the use of EPO on reproductive parameters in vivo has not yet been described. On the other hand, in vitro studies with cultured cells have shown that erythropoietin stimulates steroidogenesis in Leydig cells, triggering an increase in testosterone production. The objective of this study is to evaluate the effects of the administration of recombinant erythropoietin (rHuEpo) and erythropoietin gene transfer in reproductive parameters of rabbits. Fifteen rabbits were divided in 3 groups: group I (rHuEpo) received subcutaneously 25UI/kg of recombinant human erythropoietin, three times a week for 5 weeks; group II (pTarget/Epo) received a single dose of recombinant vector with the gene of the rabbit erythropoietin; group III (pTarget) received a single dose of empty pTarget vector (control). Throughout the experiment, reproductive and blood parameters were monitored, such as: sperm motility, spermatic vigor, sperm concentration, sperm viability, sperm morphology, erythrocytes and hematocrit level. Erythropoietin gene transfer and rHuEpo administration caused a significant increase in the number of erythrocytes. The animals which received rHuEpo showed an increase in the hematocrit level, reaching numbers between 41,34 and 52,32. The statistical analysis proved that the treatment and the time did not interfer on sperm motility, sperm concentration and spermatic vigor (P<0.05). The percentage of morphologically normal cells in group I as well as in group II decreased over time, however, there was no statistical difference between the treatments (P<0.05). This study is the first to show the answers to the use of gene doping with the erythropoietin gene and the rHuEpo administration in reproductive and blood parameters.